2021
DOI: 10.3389/fmolb.2021.784303
|View full text |Cite
|
Sign up to set email alerts
|

Computational Saturation Mutagenesis of SARS-CoV-1 Spike Glycoprotein: Stability, Binding Affinity, and Comparison With SARS-CoV-2

Abstract: Severe Acute respiratory syndrome coronavirus (SARS-CoV-1) attaches to the host cell surface to initiate the interaction between the receptor-binding domain (RBD) of its spike glycoprotein (S) and the human Angiotensin-converting enzyme (hACE2) receptor. SARS-CoV-1 mutates frequently because of its RNA genome, which challenges the antiviral development. Here, we per-formed computational saturation mutagenesis of the S protein of SARS-CoV-1 to identify the residues crucial for its functions. We used the structu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…To further determine the importance of the key residues in the interaction of compound 6b with ApisOBP3, the key residues (TYR27, LYS28, VAL29, TYR102, MET105, LEU108, and ASN109) and three other residues (VAL23, LYS25, and THR103) within the 5 Å range of compound 6b in the binding cavity of ApisOBP3 were selected to perform alanine site-directed mutagenesis. According to previous studies, , a negative value of ΔΔ G led to a more stable binding complex while a positive value of ΔΔ G indicated an unstable complex. Evaluation of the binding free energy change was categorized as follows: highly stabilizing (ΔΔ G <−2.0 kcal/mol), moderately stabilizing (−2.0 ≤ ΔΔ G <−0.5 kcal/mol), neutral (−0.5 ≤ ΔΔ G ≤ 0.5 kcal/ mol), moderately destabilizing (0.5 < ΔΔ G ≤ 2.0 kcal/mol), and highly destabilizing (ΔΔ G > 2.0 kcal/mol).…”
Section: Resultsmentioning
confidence: 77%
“…To further determine the importance of the key residues in the interaction of compound 6b with ApisOBP3, the key residues (TYR27, LYS28, VAL29, TYR102, MET105, LEU108, and ASN109) and three other residues (VAL23, LYS25, and THR103) within the 5 Å range of compound 6b in the binding cavity of ApisOBP3 were selected to perform alanine site-directed mutagenesis. According to previous studies, , a negative value of ΔΔ G led to a more stable binding complex while a positive value of ΔΔ G indicated an unstable complex. Evaluation of the binding free energy change was categorized as follows: highly stabilizing (ΔΔ G <−2.0 kcal/mol), moderately stabilizing (−2.0 ≤ ΔΔ G <−0.5 kcal/mol), neutral (−0.5 ≤ ΔΔ G ≤ 0.5 kcal/ mol), moderately destabilizing (0.5 < ΔΔ G ≤ 2.0 kcal/mol), and highly destabilizing (ΔΔ G > 2.0 kcal/mol).…”
Section: Resultsmentioning
confidence: 77%
“…We showed that the top destabilizing/stabilizing mutations have damaging effects on protein function, except for D264H, which is predicted to have neutral effects ( Table 1 ). In our previous study [ 40 ], we discovered these tools are reliable for analyzing the effects of mutations on protein function.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the aforementioned similarities, there is a similar pattern of predicted effects on the protein stability for MERS-CoV, SARS-CoV-2, and SARS-CoV S proteins. Most of the mutations we generated in the these three full-length S proteins and RBD regions were predicted to have destabilizing effects, ranging from 24 to 37.4% ( Sobitan et al, 2021 ; Teng et al, 2021 ). Mutations predicted to have a neutral effect were also similar between MERS-CoV, SARS-CoV, and SARS-CoV-2 S proteins (25.4–30%).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations predicted to have a neutral effect were also similar between MERS-CoV, SARS-CoV, and SARS-CoV-2 S proteins (25.4–30%). The percentages of stabilizing mutations generated in the three severely pathogenic coronaviruses ranged from 7.4 to 14% ( Sobitan et al, 2021 ; Teng et al, 2021 ). We found a similar distribution of free folding energy predictions for the RBD region and for the full-length S protein of MERS-CoV.…”
Section: Discussionmentioning
confidence: 99%